Editorial - Nain, M S (Indian Journal of Extension Education, 2021)
It’s my privilege to present the current issue (April-June, 2021) with a wide variety of content ranging from livelihood vulnerability analysis, mobile usage behavior, self-help groups, agricultural insurance, geography specific constraints analysis, training needs analysis, adoption status , social media usages, extension model, price behaviour, entrepreneurial economic analysis and profit relationship with attributes, effectiveness of communication methods in the context of current pandemic. Its more satisfying that authors have reoriented their research issues in light of current situations. The examination of information manipulation theory, Box-Jenkins ARIMA Approach, and designing certain measurement tools have added to the body of knowledge. T. R. Shankar Raman, a wildlife scientist with Nature Conservation Foundation has rightly advocated that if science itself has the capacity to shake free of old paradigms and shift to new realities , it can happen in the scientific publication by our far deeper commitment to and more active engagement with free and open access to science and scientific knowledge . We, at Indian Journal of Extension Education level are trying to make it fully open access through online submission and management of all content. The readers, authors and reviewers have significantly contributed towards successful implementation and need applause. Here, I appeal for more active involvement of each stakeholder in the endeavour. I extend my sincere thanks to all the authors for making valuable contributions. I also extend sincere thanks to all the expert members in the editorial board. Special thanks are extended to and Dr. Himanshu De, Dr. Lalita Vatta, Dr. Souvik Ghosh, Dr. M. C. Ahire, Dr. Jayaraghavendra Rao and so many for their painstaking efforts. Special thanks are extended to the President, ISEE; Dr US Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bring out this issue. Dr. Bhanu Mishra deserves special thanks for making committed efforts at all stages of ISEE matters. (Manjeet Singh Nain)